Optical coherence tomography angiography allows longitudinal monitoring of angiogenesis in the critical-sized defect model - Shen, Yiyang; Bu, Jin; Yu, Lan; Yao, Lin; Feng, Xiaoyan; Lin, Jun; Li, Peng (Frontiers in Physics, 2023)
This study aims to evaluate the capability of optical coherence tomography angiography (OCTA) for imaging the microvasculature within a critical bone defect, as well as to longitudinally observe vascular alterations and quantify microvascular density and morphology in a model of a critical-sized defect. Methods: An OCTA system was employed to longitudinally monitor the angiogenesis in four rat models presenting critical-sized defects with observations recorded on the 7 th , 14 th , and 28 th day post-defect creation. Simultaneously, the angiogenesis in three additional rat models was evaluated through conventional histological analysis involving hematoxylin and eosin staining. Results: The OCTA was successful in acquiring in vivo 3D vascular perfusion mapping within the critical-sized defect, and it allowed for quantitative analysis of the microvasculature's density and morphology. The OCTA imagery of blood microvasculature revealed a noticeable augmentation in the number and size of vessels , with more extensive vessel convergence observed on the 14th day compared to both the 7th and 28th day. Complementing these observations, quantitative analysis demonstrated that, the vessel area density (VAD) and maximum vascular diameter index (MVDI) were significantly larger on the 14th day in comparison to measurements taken on the 7th and 28th days.. Conclusions: Leveraging its ability to capture high-resolution images, OCTA facilitated longitudinal monitoring of angiogenesis in models of critical-sized defects. Therefore, it potentially serves as a non-invasive experimental tool beneficial for bone regeneration research.